Kepemimpinan Transformatif Ketua Program Studi dalam Pengembangan Program Studi Manajemen Pendidikan Islam - Shobri, Muwafiqus; Jaosantia, Jasmani (AKSI: Jurnal Manajemen Pendidikan Islam, 2024)
This study examines the application of transformative leadership by the head of the study program in the development of the Islamic Education Management (MPI) Study Program. Using the literature research method, this study explores the characteristics of transformative leadership, program development strategies, as well as the obstacles and opportunities faced. The results show that the transformative leadership approach that focuses on inspirational motivation, idealized influence, and intellectual stimulation is effective in improving the quality of the study program and curriculum relevance. The main strategies implemented include adaptive curriculum development, increasing lecturer competence, and external collaboration. Constraints faced include limited resources, while opportunities lie in the potential for strategic cooperation. These findings emphasize the importance of transformative leadership as a relevant leadership model in Islamic education, especially in facing the demands of academic development and market needs.